Pneumonia in acute ischemic stroke patients requiring invasive ventilation: Impact on short and long-term outcomes. Issue 3 (September 2019) - de Montmollin, Etienne; Ruckly, Stephane; Schwebel, Carole; Philippart, Francois; Adrie, Christophe; Mariotte, Eric; Marcotte, Guillaume; Cohen, Yves; Sztrymf, Benjamin; da Silva, Daniel; Bruneel, Fabrice; Gainnier, Marc; et al.
Highlights: Pneumonia occurs in 40% of ischemic stroke patients requiring invasive ventilation. Post-stroke pneumonia does not impact ICU mortality. Post-stroke pneumonia is associated with a 1.6-fold increase in ICU length-of-stay. Post-stroke pneumonia is associated with a 49% increase in 1-year mortality. Summary: Objectives: To describe the epidemiology and prognostic impact of pneumonia in acute ischemic stroke patients requiring invasive mechanical ventilation. Methods: Retrospective analysis from a prospective multicenter cohort study of critically ill patients with acute ischemic stroke requiring invasive mechanical ventilation at admission. Impact of pneumonia was investigated using Cox regression for 1-year mortality, and competing risk survival models for ICU mortality censored at 30-days. Results: We included 195 patients. Stroke was supratentorial in 62% and 64% of patients had a Glasgow coma scale score <8 on admission. Mortality at day-30 and 1 year were 56%, and 70%, respectively. Post-stroke pneumonia was identified in 78 (40%) patients, of which 46/78 (59%) episodes were present at ICU admission. Post-stroke pneumonia was associated with an increase in 1-year mortality (adjusted HR 1.49, 95%CI [1.01–2.20]). Post-stroke pneumonia was not associated with ICU mortality but was associated with a 1.6-fold increase in ICU length of stay (CSHR 0.62 [0.39–0.99], p = 0.06). Conclusions: In ischemic stroke patients requiring invasive ventilation, pneumonia occurred in 40% of cases and was associated with a 49% increase in 1-year mortality. Post-stroke pneumonia did not impact day-30 mortality but increased ICU length of stay.